2020
DOI: 10.1111/bjh.16806
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the UK myeloma research alliance risk profile, a new clinical prediction model for outcome in patients with newly diagnosed multiple myeloma not eligible for autologous stem cell transplantation; a population‐based study from the Danish national multiple myeloma registry

Abstract: In 2019 the UK Myeloma Research Alliance introduced the Myeloma Risk Profile (MRP) for prediction of outcome in patients with newly diagnosed multiple myeloma (MM), ineligible for autologous stem cell transplantation. To validate the MRP in a population-based setting we performed a study of the entire cohort of transplant ineligible MM patients above 65 years in the Danish National MM Registry. Our data confirmed the value of the MRP. In a cohort of 1,377 patients, the MRP score separated patients into three d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 13 publications
0
16
3
Order By: Relevance
“…Therefore, they showed consistent results in terms of the prognostic value of MRP score; that is, the high-risk group had a higher risk of early death and a shorter PFS. 6 They also found that the high-risk group had much higher Cr, lower Hb, and higher LDH levels, which differed from the results of our study. 6 In addition, patients in the high-risk group had shorter treatment durations and worse treatment responses.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Therefore, they showed consistent results in terms of the prognostic value of MRP score; that is, the high-risk group had a higher risk of early death and a shorter PFS. 6 They also found that the high-risk group had much higher Cr, lower Hb, and higher LDH levels, which differed from the results of our study. 6 In addition, patients in the high-risk group had shorter treatment durations and worse treatment responses.…”
Section: Discussioncontrasting
confidence: 99%
“… 6 They also found that the high-risk group had much higher Cr, lower Hb, and higher LDH levels, which differed from the results of our study. 6 In addition, patients in the high-risk group had shorter treatment durations and worse treatment responses. 6 …”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The risk profile defined by this score included both tumor characteristics (ISS stage) and host characteristics (performance status, age, CRP). The MRP score was retrospectively validated in real-life patients and will be prospectively validated and compared with the IMWG Frailty Score in the ongoing UK-MRA Myeloma XIV study (FiTNEss) [42].…”
Section: Abbreviations Who World Health Organization; Iss Internatmentioning
confidence: 99%